STUDIES OF MINERAL COMPOSITION OF ORES OF THE KUMTOR DEPOSIT (CENTRAL TIEN SHAN) BY QXRD AND XRF METHODS - A.G. Shevkunov; A.A. Guda; A.A. Skorynina; S.W. McKnight (Минералогия)
Samples of various mineral ore types of the Kumtor gold deposit (Central Tien Shan) were studied using XRF method on a TORNADO M4 analyzer by digital processing of images of the elemental scanning maps to reveal the possibilities of this method to measure the mineral composition of ores without using the AMICS electronic mineral database. During the experimental work, the optimal parameters of elemental analysis and scanning of samples were selected, which allow maximum information with minimal time and expenses. The experimental analyses enabled us to estimate the semi-quantitative content of major ore-forming non-metallic and ore minerals and to establish the possible presence of minerals previously unknown in the composition of ores (barytocalcite, viterite, ferrinatrite, etc.). The macro- and microscopical identification of these minerals is problematic, although their relative content locally reaches several weight percents.